Beetle & the Hollowbones - Layne, Aliza (Atheneum Books for Young Readers, 2020)
In the town of 'Allows, some people are magical sorceresses while others have their spirits trapped in the local mall for eternity. Twelve-year-old goblin-witch Beetle and her best friend Blob Ghost are hanging out at the mall when Beetle's best friend, Kat, arrives back in town to do a sorcery apprenticeship with her aunt Hollowbone. The friends stumble upon a plot that puts Blob Ghost in danger and while they race to save him, they find themselves falling in love.